Analisis Kesiapan Digital UMKM Trenggalek: Perspektif dari Strategi Digital Marketing - Nurastuti, Wiji; Sumiyanto, Ahmad; Hesvindrati, Netci (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This study aims to analyze the readiness of Micro, Small, and Medium Enterprises (MSME) in Trenggalek to adopt digital marketing strategies as part of their digital transformation. A quantitative approach was used, with data collected through questionnaires distributed to 44 respondents. The analyzed indicators include experience, satisfaction, interactivity, and knowledge, as well as supporting and inhibiting factors in the digital transformation process. The results indicate that MSME in Trenggalek have a relatively high level of readiness to adopt digital marketing strategies. Respondents provided positive assessments of their digital interaction experience and their ability to understand digital marketing strategies. However, the main challenges faced include limitations in technological infrastructure, access to funding, and technical skills. This study provides strategic insights to encourage the adoption of digital transformation among MSME through strengthening the digital ecosystem, improving human resource skills, and expanding technological support.